A study on prevalence of hearing impairment and ear diseases in Kelantan - Razali, Mohd Sayuti (2006)
Objective To determine the prevalence of hearing impairment and ear diseases in Kelantan. Methodology It was a prospective population based cross-sectional study. The study was conducted in the chosen subjects that based on two-stage stratified random sampling in nine districts in Kelantan. Enumeration blocks (EB) were selected from each district. Eight living quarters were selected from each EB. All households who live in the living quarters and consented to get involved in the study were screened for hearing impairment and ear diseases by using questionnaire, ear examination and audiological test at their house. Each participant was subjected to otoacoustic emission test. Subjects were then underwent behavioral test according to their age. The behavioral tests include distraction test and pure tone audiometry (air conduction only). Result A total of 502 participants were screened. For the ear diseases, 500 were able to be examined and the prevalence was 11.8o/o. Impacted wax was the most common ear disease found followed by chronic suppurative otitis media. Whereas for the hearing impairment, the prevalence based on OAE was 30.2o/o and this figure was reduced to 16.8% when the participants were screened with behavioral tests. Presbyacusis was most common finding of the cause of hearing impairment followed by noise induced hearing loss. Conclusion Result from the study has shown that significant prevalence of ear diseases and hearing impairment among population of Kelantan and effort should continue even harder to tackle the problems. Providing education toward good ear care and screening program to detect hearing impairment as early as possible and thus early rehabilitation should be carried out.